Trans effects of chromosome aneuploidies on DNA methylation patterns in human Down syndrome and mouse models. Issue 1 (December 2015) - Mendioroz, Maite; Do, Catherine; Jiang, Xiaoling; Liu, Chunhong; Darbary, Huferesh; Lang, Charles; Lin, John; Thomas, Anna; Abu-Amero, Sayeda; Stanier, Philip; Temkin, Alexis; Yale, Alexander; et al.
Abstract Background Trisomy 21 causes Down syndrome (DS), but the mechanisms by which the extra chromosome leads to deficient intellectual and immune function are not well understood. Results Here, we profile CpG methylation in DS and control cerebral and cerebellar cortex of adults and cerebrum of fetuses. We purify neuronal and non-neuronal nuclei and T lymphocytes and find biologically relevant genes with DS-specific methylation (DS-DM) in each of these cell types. Some genes show brain-specific DS-DM, while others show stronger DS-DM in T cells. Both 5-methyl-cytosine and 5-hydroxy-methyl-cytosine contribute to the DS-DM. Thirty percent of genes with DS-DM in adult brain cells also show DS-DM in fetal brains, indicating early onset of these epigenetic changes, and we find early maturation of methylation patterns in DS brain and lymphocytes. Some, but not all, of the DS-DM genes show differential expression. DS-DM preferentially affected CpGs in or near specific transcription factor binding sites (TFBSs), implicating a mechanism involving altered TFBS occupancy. Methyl-seq of brain DNA from mouse models with sub-chromosomal duplications mimicking DS reveals partial but significant overlaps with human DS-DM and shows that multiple chromosome 21 genes contribute to the downstream epigenetic effects. Conclusions These data point to novel biological mechanisms in DS and have general implications fortrans effects of chromosomal duplications and aneuploidies on epigenetic patterning.